True blue graphics (Armidale, N.S.W. : New Horizons, 1995)
A compilation of Australian images.
v. 1. Australiana -- v. 2. Education -- v. 3. Panorama.
Title from disk.
Each volume also includes the Australian graphics selection CD ROM.
"DOS/Windows/Macintosh hybrid CD ROM"
System requirements: Macintosh computer with 4mb RAM, running 6.0.7 or later ; or IBM compatible with 2mb RAM running DOS 3 or later ; or IBM compatible with 4mb RAM running Windows 3.1 or later. All with CD ROM drive and a Paint or Desk Top Publishing program.
Graphics.
Keywords: Clip art -- Software; Australia -- Pictorial works -- Software